Complications of Cerebrospinal Fluid Diversion (Shunt) Catheters: A Pictorial Essay - Rahalkar, M. D. (Indian Journal of Neurosurgery, 2018)
Ventriculoperitoneal shunt catheters are very commonly used for hydrocephalus of varying etiologies in infancy to childhood to bypass the obstruction. Few people are aware of their complications, such as infection, obstruction, malfunctioning, displacements, fluid collections, disconnections, and entry into various intra-abdominal organs. These complications and related literature and images are presented in this essay. In some cases, a radiologist can be of use to a neurosurgeon to alert what complication a given catheter has produced. The objectives are (1) to describe the types and functioning of cerebrospinal fluid diversion shunt catheters, (2) to know what can go wrong with the position and function of these catheters, and (3) to understand the specific or syndromic states of complication.
Keywords: VP shunt; complications of VP shunt; migration of VP shunt catheters; slit lateral ventricle syndrome; double ventricle syndrome